PRIVATIZATION OF SECURITY IN THE 20TH CENTURY. FROM MERCENARIES TO PRIVATE MILITARY CORPORATIONS - GOGA, Ramona Ioana (Studia Universitatis Babes-Bolyai Studia Europaea, 2018)
The present paper aims to emphasize the context of the privatization of security in the 20th century and to show the differences between these newly created corporations and the old mercenaries. Moreover, it also highlights the changing the role of mercenaries and their way of action in contemporary peripheries, which erase the idea of what they previously meant and give us a different view regarding their position in the midst of intra-state wars of the period. If in the past centuries the states were contracting mercenaries to take part in hostilities during armed conflicts, whose main motivation was to obtain personal benefits and privileges, now they would rather take into account the private security services. Furthermore, the privatization of violence and the emergence of private military corporations is described, and information is provided on one of the most well-known corporations, namely Blackwater.